Aptamer tethered bio-responsive mesoporous silica nanoparticles for efficient targeted delivery of paclitaxel to treat ovarian cancer cells - Salve, Rajesh; Kumar, Pramod; Chaudhari, Bhushan P.; Gajbhiye, Virendra (Journal of Pharmaceutical Sciences, 2023)
Ovarian cancer is the leading cause of cancer deaths in female patients. The current therapeutics in ovarian cancer are limited and inefficient in curing the disease. To tackle this, we have synthesized tetrasulfide deriv-ative of silica doped, biodegradable, glutathione-responsive targeted mesoporous silica nanoparticles modi-fied with heterobifunctional polyethylene glycol as a linker and mucin-1 aptamer for triggered paclitaxel delivery to the ovarian cancer cells. Degradable mesoporous silica nanoparticles were synthesized by a modi-fied sol-gel method with tetraethyl orthosilicate and Bis (triethoxysilylpropyl) tetrasulfide. The degradable mesoporous silica nanoparticles were characterized by dynamic light scattering, Fourier-transform infrared spectroscopy, Scanning electron microscopy and Transmission electron microscopy. The degradable mesopo-rous silica nanoparticles had good paclitaxel encapsulation efficiency and glutathione-responsive paclitaxel release ability. The glutathione utilization assay and visual destruction observed within 10 days in transmis-sion electron microscopy images confirmed the degradation of the mesoporous silica nanoparticles in the tumor cell environment. The targeted degradable mesoporous silica nanoparticles were efficiently taken up by ovarian cancer cell lines OVACAR-3 and PA-1. The cytotoxicity of bare mesoporous silica nanoparticles evaluated on NIH-3T3 cell line showed good biocompatibility (>90% cell viability). Significant toxicity on OVACAR-3 (IC50 25.66 nM) and PA-1 (IC50 42.93 nM) cell lines was observed when treated with paclitaxel-loaded targeted degradable mesoporous silica nanoparticles. Results of this study demonstrated that mucin-1 targeted, glutathione-responsive mesoporous silica nanoparticles loaded with paclitaxel had a significant antitumor effect on ovarian cancer cells. All these findings demonstrated that developed nano-formulation could be suitable for ovarian cancer treatment. & COPY; 2023 American Pharmacists Association. Published by Elsevier Inc. All rights reserved.
Keywords: Degradable; GSH; Mesoporous silica nanoparticles; Mucin-1; Ovarian cancer; Paclitaxel; Stimuli-responsive

Challenges and emerging strategies for next generation liposomal based drug delivery: an account of the breast cancer conundrum - Moudgil, Aliesha; Salve, Rajesh; Gajbhiye, Virendra; Chaudhari, Bhushan P. (Chemistry and Physics of Lipids, 2023)
The global cancer burden is witnessing an upsurge with breast cancer surpassing other cancers worldwide. Furthermore, an escalation in the breast cancer caseload is also expected in the coming years. The conventional therapeutic regimens practiced routinely are associated with many drawbacks to which nanotechnological in-terventions offer a great advantage. But how eminent could liposomes and their advantages be in superseding these existing therapeutic modalities? A solution is reflected in this review that draws attention to a decade-long journey embarked upon by researchers in this wake. This text is a comprehensive discussion of liposomes, the front runners of the drug delivery systems, and their active and passive targeting approaches for breast cancer management. Active targeting has been studied over the decade by many receptors overexpressed on the breast cancer cells and passive targeting with many drug combinations. The results converge on the fact that the actively targeted formulations exhibit a superior efficacy over their non-targeted counterparts and the all lipo-somal formulations are efficacious over the free drugs. This undoubtedly underlines the dominion of liposomal formulations over conventional chemotherapy. These investigations have led to the development of different liposomal formulations with active and passive targeting capacities that could be explored in depth. Acknowl-edging and getting a deeper insight into the liposomal evolution through time also unveiled many imperfections and unchartered territories that can be explored to deliver dexterous liposomal formulations against breast cancer and more in the clinical trial pipeline.
Keywords: Breast cancer; Liposomal metamorphosis; Receptor-ligand dynamics; Targeted Drug Delivery